Wicker, Peasant Life and Instituto del Inquilino in the 1940s - Sosa-Vota, M (UNIV SANTIAGO DE CHILE, 2025)
In the early 1940s, the Instituto de Informaci & oacute;n Campesina launched the collection El libro del huaso chileno along with a series of free distribution booklets that complemented its content and were frequently promoted in its pages, one of which was Mimbre, from the year 1941. This initiative was part of a communication and educational strategy aimed at improving rural living standards, with a focus on promoting home industries, especially wickerwork, recognized for its economy and practicality in rural areas. Drawing on these sources, this study will investigate the role of home industries, exploring how wickerwork was presented as a tool to improve the well-being of peasant families, while also analyzing why, from the capital and state institutions, the use of artisanal work rooted in Chilean rural traditions was encouraged. It is argued that wicker production promoted material well-being by being tied to peasant identity and was aligned with one of the Inquilino s Institute objectives: to positively value rural life and discourage migration to the cities.